Upgraded Analytical Gas Composition Technique in the Tritium Fuel Cycle of JET. (19th May 2017) - Romanelli, S. G.; Tulloch, R.; Withycombe, A.; Hollingsworth, A.; Wakeling, B.; Camp, P. G.; Smith, R.
Abstract: The JET Active Gas Handling System has designed and commissioned a new analytical gas chromatography system. The novel design included modification of a basic off-the-shelf gas chromatograph to become tritium compatible and incorporated customised hardware of seven detectors, seven switching valves and seven separation columns into one analytical gas analyser. The functionality of the new system was proven during the inactive commissioning phase and gas species including hydrogen isotope molecules (H2, HD and D2 ), air components and hydrocarbons up to decane, water and ammonia including mass spectrum data could successfully be analysed. The design of this system is unique and the first of its kind employed in a nuclear fusion laboratory.